Classical mesoscopic effect in the resistance of point contacts - Kolesnichenko, Yu.A.; Omelyanchouk, A.N.; Yanson, A.I.; N. van der Post (Физика низких температур, 1997)
The mesoscopic effect of the dependence of the point-contact conductance on the spatial distribution of the impurities is theoretically studied. It is shown that the resistance dependence on the diameter d is not only determined by the electron mean free path lι but also by the average distance between the impurities. In the case of two types of impurities with different concentrations the mesoscopic effect is predicted for a dirty point contact (d >> lι) due to the scattering at specific (e.g magnetic) impurities with a low concentration. Such contacts were numerically modeled tor random distributions of the two types of impurities.